2022
DOI: 10.3390/cancers14205118
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanistic Roles of Sirtuins in Breast and Prostate Cancer

Abstract: Mammalian sirtuins (SIRT1–7) are involved in a myriad of cellular processes, including apoptosis, proliferation, differentiation, epithelial-mesenchymal transition, aging, DNA repair, senescence, viability, survival, and stress response. In this review, we discuss the current information on the mechanistic roles of SIRT1–7 and their downstream effects (tumor promotion or suppression) in cancers of the breast and prostate. Specifically, we highlight the involvement of sirtuins in the regulation of various prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 231 publications
(273 reference statements)
0
8
0
Order By: Relevance
“…Class III histone deacetylase (SIRT-1) plays a role in several biological processes, including DNA repair, cancer, and cell survival and proliferation. 10 This study demonstrated that serum SIRT-1 levels in BC patients were considerably higher than in healthy subjects. Multiple human cancers, including prostate cancer, colon cancer, and hepatocellular carcinoma, have been linked to increased SIRT-1 expression.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Class III histone deacetylase (SIRT-1) plays a role in several biological processes, including DNA repair, cancer, and cell survival and proliferation. 10 This study demonstrated that serum SIRT-1 levels in BC patients were considerably higher than in healthy subjects. Multiple human cancers, including prostate cancer, colon cancer, and hepatocellular carcinoma, have been linked to increased SIRT-1 expression.…”
Section: Discussionmentioning
confidence: 64%
“… 9 Based on the tumor types’ microenvironment, upstream regulators, and downstream target genes, the function of SIRT-1 is still controversial. 10 Transforming growth factor-beta (TGF-β) is a cytokine that controls how cells behave. It has numerous ways it affects epithelial cells and cell clusters that develop into carcinomas both in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we found that hypophyllanthin and phyllanthin treatment alone or in combination with DOX are significantly downregulating the expression of SIRT1 and its downstream activity marker, p-Akt protein, in MCF7 ADR cells, providing a new insight into the potential use of hypophyllanthin and phyllanthin in the treatment of resistant breast cancer phenotype. In addition, SIRT1 signaling is reported to be associated with EMT transcriptional factors in cancer, which in turn enhances cancer cell migration, invasion, and metastasis. , EMT is a biological transformation of epithelial cells to mesenchymal cells through which cellular polarity and connections are lost, which leads to stronger migratory and invasive cancer cell properties. EMT not only promotes metastasis of cancer cells but also enhances the development of DOX resistance .…”
Section: Discussionmentioning
confidence: 99%
“…[35] SIRT2, a NAD-dependent deacetylase, plays a multifaceted role in breast tumors, with evidence suggesting both oncogenic and tumor-suppressive functions. [36] In the context of cisplatin-induced renal fibrosis, berberine has been found to alleviate fibrotic processes by upregulating DUSP6 while inhibiting P2X7R, p-ERK1/2, MDM2, and SIRT2. [37] Additionally, our docking analysis revealed a particularly strong binding affinity between berberine and SIRT2.…”
Section: Discussionmentioning
confidence: 99%